2022
DOI: 10.1002/adom.202102319
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Phosphorescence from Cocrystallization of Atomic Precise Silver Nanoclusters with Tartaric Acid

Abstract: Recently, chirality was successfully introduced to rare earth complexes, which have long afterglow phosphorescence, by ball-milling with l/d-cysteine, leading to CPP with a dissymmetry factor (g lum ) up to 10 −2 . [16] CPP from multiple metal centers has also been achieved by the preparation of a homochiral metal-organic framework. [17] Despite these fantastic examples, the candidates for creating CPP are still limited. New candidates with a long lifetime and intrinsic phosphorescence are urgently needed to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…2,55 Copper based metallogels have numerous applications like redox activity, 56 proton conductivity, 57 self-healing property, 58,59 catalysis, 60 superconductor, 61 and harmful organophosphate sensing. 62 Currently, researchers are continuously trying to discover new functional materials for energy related applications to meet the worldwide energy demand with energy storage devices, 63,64 energy conversion devices, 65 solar cells, 66,67 low-friction materials, 68,69 corrosiveresistant coating, 70,71 organic photovoltaic devices, [72][73][74][75] photodetectors, 76,77 fuel cells, 78 water splitting, 79 thin-film solar cells, [80][81][82] light-emitting devices, 83 metal-organic gels to nanoclusters, [84][85][86] and so on. In 2012, Dastidar et al published an article on tartaric acid-based ligand-mediated gel materials.…”
Section: Introductionmentioning
confidence: 99%
“…2,55 Copper based metallogels have numerous applications like redox activity, 56 proton conductivity, 57 self-healing property, 58,59 catalysis, 60 superconductor, 61 and harmful organophosphate sensing. 62 Currently, researchers are continuously trying to discover new functional materials for energy related applications to meet the worldwide energy demand with energy storage devices, 63,64 energy conversion devices, 65 solar cells, 66,67 low-friction materials, 68,69 corrosiveresistant coating, 70,71 organic photovoltaic devices, [72][73][74][75] photodetectors, 76,77 fuel cells, 78 water splitting, 79 thin-film solar cells, [80][81][82] light-emitting devices, 83 metal-organic gels to nanoclusters, [84][85][86] and so on. In 2012, Dastidar et al published an article on tartaric acid-based ligand-mediated gel materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have revealed that the CD amplification of luminescent nanomaterials could be mainly attributed to an aggregation process. [40][41][42] In our study, the Au(I)-SG complexes demonstrated a high degree of flexibility in the non-aggregate state, leading to significant vibrational and rotational intensities of the synthesized Au(I)-SG oligomers. Conversely, the aggregate state of AuNCs showed inter-and intra-cluster aurophilic interactions coupled with intramolecular H-bonds that could efficiently restrict the vibrational and rotational transitions of the chiral GSH ligands, and thus the CD signals were highly amplified.…”
Section: Chirality Enhancement Effectmentioning
confidence: 71%
“…Gold nanoclusters (AuNCs) represent a prominent class of organic–inorganic composite materials. The unique photoluminescence (PL) properties of AuNCs, such as phosphorescence, size-dependent luminescence, and long wavelength (red/near-infrared) emission, make them promising candidates in various fields, including chemical sensing, bioimaging, and optoelectronic devices. However, the low quantum yield (QY) restricts their practical applications. Moreover, various tuning strategies to improve the emission properties of AuNCs, enhance the electron density of thiolate ligands, regulate the polarity of solvents, and regulate the ratio of metal atoms to ligands or co-assembly with other molecules have been successfully proposed. Those strategies could overcome the drawbacks, and materials with a relatively long lifetime of microseconds assigned to phosphorescence can be obtained.…”
Section: Introductionmentioning
confidence: 99%